Digital Atlas of GAM 2013 Plan - Soto-Montoya, Casia (2014)
In 2012 a colaboration process between ONU-Habitat, Technological Institute of Costa Rica, the Ministry of Housing and Human Settlements and the National Institute of Housing and Urban Development, was oficıalızed under he cordination of Secretariat of Urban Development Plan (SPNDU) the initiative called Plan GAM 2013. To consolidate the proposals and objectives to achieve this plan was necessary to generate a GIS tool able to analyze and visualize the technical content of the planning and zoning, to achıeve this objective, software and hardware available in the SPNDU and the National Center for High Technology (CeNAT) was used, also a methodology that included the compilation and diagnosis of existing information, the creation of a data dictionary, standardization of cartographic elements, metadata development and the generation of new layers. The result of this approach was a simple database, accessible, easy to use with the potential to replicate, which was incorporated into a digital atlas with 83 maps and 172 layers of geographic information. The use of this digital atlas allowed an efficient analyze of the situation at the greater metropolitan area in Costa Rica.